ANALISIS VARIASI CAMPURAN BERAT TANAH HUMUS DAN KOMPOS TERHADAP PENURUNAN TOTAL PETROLEUM HIDROKARBON (TPH) DENGAN KONSEP BIOREMEDIASI DI PT. AURORA WORLD CIANJUR - R. Siti Mardiyanti Pratiwi; Yosephina Adriani S; Achmad Taufik (Poltekkes Kemenkes Bandung, 2019)
Aurora World Cianjur Inc. is one of the manufacture industry who produce dolls in Indonesia. On the process production they use 1446 sewing machine and 5 compressor machine. Compressor machine used in stuffing process and the outcomes are Â± 70 liter/18 month lubricating oil that have not been processed before. Lubricating oil is a derivative from curde oil and the greatest content is hydrocarbon compounds. The target from this research is to know the variation of weight mixture of topsoil and compost give effect to reducing the concentration of Total Petroleum Hydrokarbons (TPH) with bioremediation concept in Aurora World Cianjur Inc. The type of this research is pretest-posttest with control group. The population is all the lubricating oil of usage sewing maching and compressor machine and the sample is lubricating oil of usage compressor machine from 2016 until April 2017. Technique intake sample with random sampling by homogenizing first the lubricating oil then weighted 3 kg for each repetition. Data proceccing using SPSS with the Kuskall-Wallis test. TPH concentration before being treated is 90,47% and then after treatment for 30 days with variation 1 (3 kg 6 kg) the concentration 13,295% on variation 2 (4.5 kg 4.5 kg) TPH concentration is 12,305% and TPH concentration for the last variation or variation 3 (6 kg 3 kg) is 9,372%. Based on the test with Kruskall-Wallis obtained p.value < Î± (0,001 < 0,005). Data analysis results show the variation of weight mixture of topsoil and compost give effect to decrease the concentration of Total Petroleum Hydrokarbons (TPH) with bioremediation concept in Aurora World Cianjur Inc.